Strategic Environmental Policy Analysis in Gunung Mas Regency, Central Kalimantan - Muhammad Imanuddin Kandias Saraan; Miswanto; Ferry Setiawan (Talenta Publisher, 2026)
This study aims to analyze the integration of strategic environmental policies into development planning in Gunung Mas Regency, Central Kalimantan, by highlighting the effectiveness of the implementation of Strategic Environmental Assessment (KLHS) in the Regional Medium-Term Development Plan (RPJMD). Using a prospective approach based on SMIC-PROB Expert, this study evaluates the most likely policy scenarios and their systemic impacts on sustainable development. Simulation results indicate that the stagnant scenario (00000) has the highest probability of 53.4%, reflecting weak integration and synergy across sectors. Sensitivity and dependency analyses indicate that strengthening sustainable agricultural systems is the most influential variable, while community-based ecotourism development is the most dependent. This study recommends reformulating regional policies by placing KLHS as the primary instrument, improving environmental governance based on spatial data, and developing five priority interventions: land and forest rehabilitation, sustainable agriculture, community ecotourism, green infrastructure, and integrated waste and sewage management. This study emphasizes the need for policy transformation from a normative-sectoral approach to a systemic, mission-driven, and inclusive strategy to achieve low-carbon and sustainable development at the regional level.